Localized modification of graphene oxide properties by laser irradiation in vacuum. (July 2019) - Cutroneo, M.; Torrisi, L.; Havranek, V.; Mackova, A.; Malinsky, P.; Torrisi, A.; Silipigni, L.; Fernandes, S.; Sofer, Z.; Stammers, J.
Abstract: Modifications induced by nanosecond Nd:YAG laser irradiation in the graphene oxide properties were investigated. To correlate the effects of laser irradiation with the modifications of the structural, chemical and electrical properties of graphene oxide, 2.5 MeV alpha particle and 2.0 MeV proton beams in Rutherford backscattering spectrometry and elastic recoil detection analysis, and also X-ray photoemission spectroscopy, have been employed. A high ratio of carbon to oxygen atoms was measured in the irradiated graphene oxide, with respect to the virgin one. The localized reduction of graphene oxide film is promising for patterning techniques useful for the graphene-based devices production. Highlights: Modification of Graphene oxide (GO)structure to tailor its properties. Laser irradiation as promising method for localized modification of GO. IR laser treatment to induce localized heating in the GO surface. Partial conversion of GO in rGO induced by laser irradiation.